Just Clean Enterprise / Khadijah Safiyyah Baharudin ... [et al.] - Baharudin, Khadijah Safiyyah; Abdul Aziz, Nuralia Anastasia; Sahah, Nurul Afifi; Asri, Nor Yusrina Yuhanis (2021)
Just Clean will provide house cleaning services for anyone who requires assistance in cleaning their house or who does not have time to do it due to their respective jobs. It specializes in high-end cleaning services by offering professional, trustworthy, efficient, and effective services that will enable it to quickly grow in business. We chose to open our company in Penang because we thought Penang was a strategic area for our business and many people in that area needed our services. Plus, there are a lot of people who are always busy with their work and do not have time to manage their houses. So, Just Clean will help them clean their houses at an affordable price. In addition, financial planning is an important element for us to start a business as a start-up capital. As far as setting up the business itself, we need financial resources to cover the basic costs of setting up a business, including the cost of business registration, telephone line registration, water, name cards, office or building rent, and management expenses. Furthermore, a successful organization is also a key resource for business. The success of an organization depends on the talent and strength of its employees. In conclusion, the business plan was very important for a new company like "Just Clean Enterprise" because it may help us to maintain our business longer in the Malaysia market. The purpose of this business plan was to show the financial strength of the company, especially when applying for loans, and to convince investors to provide funds or other financial institutions that will assist us in running our business. Then, it became a guideline for us in setting, planning, handling, and controlling our business for day-to-day management, budget, financial forecast, strategies, target market, and even long-term goals. Next, it also improves any weaknesses arising by comparing the actual performance of the firm with a favourable or unfavourable situation.